Inhibitory effect of toothbrush monofilament containing surface pre-reacted glass-ionomer (S-PRG) filler on Streptococcus mutans - Matayoshi, Saaya (Sci Rep, 2021)
The oral environment affects not only oral health, but also general health, and the importance of oral self-care has recently been recognised. Although toothbrushes are the most important self-care product, there are few toothbrushes that have an inhibitory effect on oral bacteria. In the present study, monofilaments used for toothbrushes containing surface pre-reacted glass-ionomer (S-PRG) filler (a component recently applied to various dental materials) were developed. Among nylon and polyester monofilaments commonly used for toothbrushes, nylon monofilaments can accommodate more S-PRG filler than polyester monofilaments, resulting in greater release of ions from the S-PRG filler. These monofilaments containing S-PRG filler formed less biofilm containing Streptococcus mutans, a major pathogen of dental caries, than monofilaments without S-PRG filler. Moreover, S. mutans adhering to monofilaments containing S-PRG filler were more easily exfoliated and eliminated than those adhering to monofilaments without S-PRG filler. Such inhibitory effects on S. mutans were more marked in nylon monofilaments than in polyester monofilaments. These findings that monofilaments containing S-PRG filler can release ions and have an inhibitory effect on S. mutans suggest that they may be an effective material for toothbrushes.